UNITED VOICES: EXPLORING COMMUNITY SOLIDARITY IN MEENA KANDASAMY’S THE GYPSY GODDESS - Mourine Nikita.C; V. Rejulin Jerin Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In The Gypsy Goddess, Meena Kandasamy examines the subject of community harmony as a powerful response to the systemic oppression faced by Dalits in contemporary India. Through the depiction of collective struggles and shared histories, Kandasamy illustrates how marginalized individuals come together to forge a unified identity in the face of adversity. The novel is anchored in the historical context of the Kilvenmani massacre, serving as a touching reminder of the violent repression of Dalit agricultural labourers. Kandasamy emphasizes the importance of collective memory, emotional bonds, cultural resistance and the role of women in fostering solidarity. All the women characters embody resilience, challenging traditional gender roles and engaging actively in protests to demand justice and dignity. The narrative intertwines personal and collective memory, showcasing how these shared experiences empower the community to confront the oppressive structures of caste. By exposing the community solidarity, Kandasamy not only highlights the strength found in unity but also advocates for a transformative collective identity that challenges in making the novel a significant contribution to contemporary discussions on caste, resistance and social justice.